O projeto de paz de Oslo: considerações e críticas sobre as origens do processo de paz Israel-Palestina (1991-1995) - Saab, Luciana (2016)
This paper refers to the signing of the Oslo Accords between Israel and the Palestinians in September 1993 from the understanding that the necessary terms in order to solve the historical conflict are not discussed in the peace process. The reading of the first document to be signed, the Declaration of Principles (DOP), reveals that the contents of the peace proposal and the bilateral negotiations formula do not alter the existing asymmetry of power between Palestinians from the PLO and the State of Israel, which makes the uneven process extremely favorable to the continuation of the Israeli military occupation over the territories of Gaza and the West Bank. The paper therefore focuses its analysis on the negotiation process previous to the signing of the DOP and the political and economic context of those responsible for Oslo, in order to establish what were the interests involved and how they influenced the drafting of the terms of the Declaration. During the research, it becomes clear that the Oslo agreements only benefited the actors involved in secret negotiations in Norway, namely the PLO and Israeli Labor Party, which allows us to state that the peace process was not representative of the various Palestinian and Israeli political sectors. The study also reveals that the peace proposal made to the Palestinians in Oslo is an Israeli formulation, that refers back to the beginning of the peace process in the Middle East in 1978, whose main goal was the normalization of diplomatic relations between Israel and the Arab neighboring states . Thus, the conditions discussed in Oslo were based on an old assumption that regional peace does not imply in the creation of a Palestinian state, but only the right to self-representation of the Palestinian residents in the occupied territories. These conditions were accepted by Yasser Arafat as a strategy to gain political prestige and return to the territory of Palestine. We conclude therefore that the Oslo peace process was not a legitimate initiative to establish a fair and equal peace in the region, as claimed by Israel and the United States, but an agreement made between the Israeli Labour Party and the PLO, drafted to enabled the Israeli territorial expansion over the West Bank and Gaza, to dismiss the question of refugees and not recognize the Palestinian’s right to national self-determination